REPRESENTASI PERILAKU GENERASI Z DAN GENERASI MILENIAL DALAM NOVEL TIMUN JELITA VOL 2 KARYA RADITYA DIKA: PENDEKATAN SOSIOLOGI SASTRA - Neneng Ratnadila; Nori Anggraini (Jurnal Lazuardi, 2026)
This research article aims to examine Raditya Dika's novel entitled Timun Jelita Vol 2. The things that will be studied in this novel are the intrinsic elements and sociology of literature with a scope of discussion such as the author's social context, the depiction of society in the novel, and the social values ​​contained in the novel. The novel Timun Jelita Vol 2 is a comedy genre novel that presents many interesting events that occur in the novel. The analysis used Wellek & Warren's sociological literary approach. This article uses a qualitative descriptive method to present data in the form of descriptions to the maximum. The data collection techniques applied in this article are reading, listening, and taking notes. The results of the research presented are part of the intrinsic elements in the form of themes, plots, settings, characters and characterizations as well as the message conveyed by the author. In addition, the results of the research conducted present a picture of society in the novel, the author's social context and social values ​​in the novel such as the value of compassion, the value of solidarity and also the value of struggle represented by the characters in the novel.